Shelf control in retail stores via ultra-low and low power microcontrollers - ÜNSALAN, CEM (My University, 2022)
Smart retail stores started to take place in our lives. Several computer vision and sensor-based systems are working together to achieve such a complex and automated operation. Besides, the retail sector has several open and challenging problems which can be solved by embedded computer vision systems. One important problem to be tackled is shelf control or stock out detection. Here, shelves in a store should be controlled regularly such that no item is missing in the shelf. In this study, we propose an embedded computer vision system to solve this problem. To do so, we frame the shelf control operation as change detection. Due to the constraints posed by the retail sector, we formed the system by an ultra-low or low power microcontroller with an embedded camera attached to it. We provided all the implementation details of the system both from software and hardware perspectives. We also tested the proposed shelf control system from different perspectives. Hence, the reader can form such a system for retail sector or for a broad class of change detection problems in which stand-alone embedded system usage is mandatory.
Keywords: Tıp; Sağlık Bilimleri; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Medicine; Health Sciences; Information Systems, Communication and Control Engineering; Signal Processing; Computer Sciences; algorithms; Engineering and Technology; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Mühendislik; GÖRÜNTÜLEME BİLİMİ VE FOTOĞRAF TEKNOLOJİSİ; Klinik Tıp; Klinik Tıp (MED); COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); ENGINEERING, ELECTRICAL & ELECTRONIC; ENGINEERING; IMAGING SCIENCE & PHOTOGRAPHIC TECHNOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Mühendislik; Yapay Zeka; Genel Bilgisayar Bilimi; Mühendislik (çeşitli); Elektrik ve Elektronik Mühendisliği; Bilgisayar Bilimi (çeşitli); Bilgisayarla Görme ve Örüntü Tanıma; Bilgisayar Bilimi Uygulamaları; Fizik Bilimleri; General Engineering; Artificial Intelligence; General Computer Science; Engineering (miscellaneous); Electrical and Electronic Engineering; Computer Science (miscellaneous); Computer Vision and Pattern Recognition; Computer Science Applications; Physical Sciences; Shelf control; Retail sector; Change detection; Microcontroller implementation